The bacteriostatic activity of essential oils for some specimen Millefolium Koch. genus Achillea L. - G. P. Smoilovskaya; A. V. Mazulin; O. M. Svetashov (Zaporozhye State Medical University, 2014)
Pharmacologic effect of herbal drugs is associated with the availability in its composition the complex of biologically active substances, particularly, the essential oils, which are capable to suppress the multiplication of many microorganisms, fungi, viruses. Aim. To determine the bacteriostatic activity of essential oils of Millefolium subvulgare and Millefolium setaceum have been studied physic - chemical characters, identification and quantitative content of constituents of the essential oils obtained has been carried out by gas chromatography mass-spectrometry. Methods and results. It has been identified in the composition of the essential oil from Achillea setacea Waldst. et Kit 63 substances, 57 substances for Achillea submillefolium Klok. et Krytzka, azulene derivatives were predominant. The subsequent bacteriostatic studies for essential oils revealed their pronounced bacteriostatic activity for Staphylococcus aureus, mixt- flore1, Pseudomonas aeruginosa, Streptococcus pyogenes, Escherichia coli. Conclusion. The essential oil from Millefolium subvulgare demonstrated the more intensive activity associated with the predominance of azulene derivatives.